2016
DOI: 10.1108/lhs-11-2014-0072
|View full text |Cite
|
Sign up to set email alerts
|

Management and leadership competence in hospitals: a systematic literature review

Abstract: Purpose - The purpose of this study is to describe the characteristics of management and leadership competence of health-care leaders and managers, especially in the hospital environment. Health-care leaders and managers in this study were both nursing and physician managers. Competence was assessed by evaluating the knowledge, skills, attitudes and abilities that enable management and leadership tasks. Design/methodology/approach - A systematic literature review was performed to find articles that identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 45 publications
(91 reference statements)
3
59
1
17
Order By: Relevance
“…Whilst there is recognition that the demands made on a manager will vary dependant on the context and their particular role, considerable work has been done to clarify what competences are required by managers within healthcare settings [13,18,28,30,31,49,56]. Pihlainen et al (2016)'s [57] systematic review suggests that competences related to the healthcare context have social, organisational, and financial dimensions, and that these should be demonsrated alongside operational (i.e. quality improvement, credibility with professionals, and staff development) and general management (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Whilst there is recognition that the demands made on a manager will vary dependant on the context and their particular role, considerable work has been done to clarify what competences are required by managers within healthcare settings [13,18,28,30,31,49,56]. Pihlainen et al (2016)'s [57] systematic review suggests that competences related to the healthcare context have social, organisational, and financial dimensions, and that these should be demonsrated alongside operational (i.e. quality improvement, credibility with professionals, and staff development) and general management (i.e.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…However, one study reported that 18.5% of nursing managers stated that time management was the most difficult issue (Lv, ). Existing studies also show a close correlation between nursing managers' time management and the following factors: gender, job experience, taking a time management course, reading books, planning skills, organizational ability and a strong sense of responsibility (Belal Said, ; Ebrahimi et al, ; Kelly & Johnson, ; Kong, ; Pihlainen, Kivinen, & Lammintakanen, ; Sköld & Janeslätt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different health systems operate in multifaceted, intertwined and dynamic networks of systems,5 which have resulted in complex processes of leadership. These are reflected by the combinations of different leadership styles, various coalitions of stakeholders with the same vision and the distribution of leadership between different individuals 6,7.…”
Section: Introductionmentioning
confidence: 99%